PRAWO DO URLOPU OJCOWSKIEGO W POLSKIEJ REGULACJI PRAWNEJ - Serafin, Katarzyna (Zeszyty Prawnicze, 2016)
THE RIGHT TO PATERNITY LEAVE UNDER THE POLISH LEGISLATION Summary By virtue of The Act of 8th December 2008 amending the Labour Code a new legal institution – paternity leave has been introduced into Polish labour law. Since 1st January 2010 an employee-father is entitled to paternity leave upon the event of childbirth. This right is not assignable. Furthermore, it is irrespective of other parental rights. The father may use the right to paternity leave by the time the child is twelve months old. During the use of that leave the father is protected against the termination of labour contract. Under the article 1823 of the Labour Code an employee has the right to paternity leave in the amount of two weeks. However, according to provisions of The Act of 8th December 2008, the above mentioned duration of paternity leave will be in force from 1st January 2012. Until that date the father is entitled to one week of paternity leave only. Introduction of the paternity leave into the Polish labour law should be approved. However, it seems that the reading of that new regulation as well as the legal constructions adopted for the purpose of an effective use of the right to paternity leave may cause some doubts and interpretative problems. The paper is an attempt of a general analysis of all provisions of the Labour Code regulating the use of right to paternity leave.